2011
DOI: 10.1177/0194599810392878
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Features of the Intraosseous Lipoma of the Sphenoid

Abstract: IOL is believed to be a more common benign intraosseous lesion within the skull base than previously reported. Cortical bone thinning and other features normally suggestive of aggressive pathology commonly occur. Otolaryngologists should be aware of these common lesions to avoid unnecessary further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 28 publications
0
27
0
9
Order By: Relevance
“…According to Milgram classification, our patient belongs to stage III with focal calcification and cystic degeneration but without bone expansion and bone destruction [9, 10]. Recent reports revealed that sphenoid localisation is rare but was not so, as it was previously suggested [1, 4, 11, 12]. Intraosseous lipoma represents 0,1% of the primary bone tumours.…”
Section: Discussionmentioning
confidence: 78%
“…According to Milgram classification, our patient belongs to stage III with focal calcification and cystic degeneration but without bone expansion and bone destruction [9, 10]. Recent reports revealed that sphenoid localisation is rare but was not so, as it was previously suggested [1, 4, 11, 12]. Intraosseous lipoma represents 0,1% of the primary bone tumours.…”
Section: Discussionmentioning
confidence: 78%
“…9 Although intraosseous lipoma can exhibit some overlapping characteristics with arrested pneumatization, such as internal mineralization, fat content, increased signal intensity on MRI-T1, and decreased intensity on MRI-T2 fat saturation; these lesions are commonly expansile, a characteristic which allows them to differentiated from arrested pneumatization. In addition, intraosseous lipomas in the maxillofacial region arise in the maxilla and the mandible 17 more frequently than in the bones of the central skull base.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the imaging features of this entity can closely mimic other benign fat-containing or ominous skull base lesions such as intraosseous lipoma, intraosseous hemangioma, hamartoma, fibrous dysplasia, and chordomas. [8][9][10] Arrested pneumatization of the skull base is not well recognized among dentists and can often be confused with other pathologies associated with the skull base, which may lead to unnecessary invasive diagnostic procedures or interventions. As a result of greater appreciation of this entity by radiologists and higher resolution cone-beam computed tomography (CBCT), computed tomography (CT), and magnetic resonance image (MRI) scans, arrested pneumatization of the paranasal sinuses is now thought be significantly more common than previous estimates indicated and is thought to be underreported.…”
mentioning
confidence: 99%
“…Involvement of the skull is even rarer [5-7]. To best of our knowledge, 12 cases of sphenoidal bone involvement have been reported in the literature [8]; among them 2 cases have been shown to involve sphenoclival area [9, 10]; hence, we are reporting the third case of sphenoclival intraosseus lipoma.…”
Section: Introductionmentioning
confidence: 99%